2003
DOI: 10.1046/j.1471-4159.2003.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous mitochondrial oxidative stress: neurodegeneration, proteomic analysis, specific respiratory chain defects, and efficacious antioxidant therapy in superoxide dismutase 2 null mice

Abstract: Oxidative stress and mitochondrial dysfunction have been linked to neurodegenerative disorders such as Parkinson's and Alzheimer's disease. However, it is not yet understood how endogenous mitochondrial oxidative stress may result in mitochondrial dysfunction. Most prior studies have tested oxidative stress paradigms in mitochondria through either chemical inhibition of specific components of the respiratory chain, or adding an exogenous insult such as hydrogen peroxide or paraquat to directly damage mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 54 publications
9
134
1
1
Order By: Relevance
“…Bcl-2 prevents activation of caspases involved in apoptosis, including caspase-3 and -9, by inhibition of cytochrome c release and by binding to apoptotic protease activating factor 1 (Murphy, 1999). SOD2, is a mitochondrial enzyme that protects against superoxide radicals that are normal by-products of cellular metabolism but can produce cell damage (Hinerfeld et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 prevents activation of caspases involved in apoptosis, including caspase-3 and -9, by inhibition of cytochrome c release and by binding to apoptotic protease activating factor 1 (Murphy, 1999). SOD2, is a mitochondrial enzyme that protects against superoxide radicals that are normal by-products of cellular metabolism but can produce cell damage (Hinerfeld et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2, CREB, and NF-κB can enhance anti-apoptic actions by inducing expression of anti-apoptotic Bcl-2 proteins and antioxidant enzymes such as manganese superoxide dismutase (SOD2) that protect against superoxide radicals (Hetman and Gozdz, 2004;Hinerfeld et al, 2004;Martinou et al, 1994;Mattson et al, 1997;Mattson and Meffert, 2006). The increased levels of ERK1/2, CREB, and NF-κB coupled with the increased levels of the neuronal protein enolase and glial protein GFAP suggested that these downstream neuroprotective proteins could also be altered by chronic CXCL10.…”
Section: Chronic Cxcl10 Increases Expression Of Anti-apoptotic Proteimentioning
confidence: 99%
“…In Caenorhabditis elegans, deletion of SOD genes leads to unexpected results; absence of SOD2 gene causes an increase and simultaneous deletion of all five SOD genes causes no shortage in the lifespan [15]. It has been reported that Drosophila null mutations for either the cytoplasmic Cu/ZnSOD or the mitochondrial MnSOD greatly decreases viability and the life span [16], however in mice only SOD2 mutation has a severe effect [17,18]. Thus, regulation of the life span by SODs is a controversial issue in different organisms and further characterization of SOD deficient cells needs to be performed to understand the ambiguities regarding their regulatory roles in the life span.…”
Section: Resultsmentioning
confidence: 99%
“…Free radicals and reactive oxygen species (ROS) have been reported for their contribution to neuronal loss in cerebral ischemia, seizure disorders, schizophrenia, PD and AD (Floyd and Carney, 1992;Good et al, 1996;Christen, 2000;Barja, 2004;Hinerfeld et al, 2004). A growing body of evidences implicates oxidative stress as being involved in the propagation of cellular injury that leads to neuropathology in these various conditions (Good et al, 1996;Christen, 2000;Andersen, 2004).…”
Section: Pro-apoptotic Role Of Rheb Role In Oxidative Stress and Agingmentioning
confidence: 99%
“…Neurons are considered to be more susceptible to oxidative damage as compared to cells in other tissues (Barja, 2004;Gille et al, 2004;Hinerfeld et al, 2004). ROS can initiate a cascade of reactions that leads to neuronal cell death (Floyd and Carney, 1992;Berlett and Stadtmann, 1997;Uttara et al, 2009).…”
Section: Pro-apoptotic Role Of Rheb Role In Oxidative Stress and Agingmentioning
confidence: 99%